2013
DOI: 10.1128/aem.02937-13
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Based Analysis of the Intestinal Microbiota of Sows and Their Offspring Fed Genetically Modified Maize Expressing a Truncated Form of Bacillus thuringiensis Cry1Ab Protein (Bt Maize)

Abstract: eThe aim was to investigate transgenerational effects of feeding genetically modified (GM) maize expressing a truncated form of Bacillus thuringiensis Cry1Ab protein (Bt maize) to sows and their offspring on maternal and offspring intestinal microbiota. Sows were assigned to either non-GM or GM maize dietary treatments during gestation and lactation. At weaning, offspring were assigned within sow treatment to non-GM or GM maize diets for 115 days, as follows: (i) non-GM maize-fed sow/non-GM maize-fed offspring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
5
13
0
Order By: Relevance
“…observed in these fermentations appear to be a normal part of the porcine healthy gut microbiota, as they were present in high numbers in the baseline group and grew to high numbers in the control group, an observation consistent with the findings of other studies in healthy animals (56,59,63,64). In the absence of genuine illness, the actual implications of Clostridium populations are difficult to discern, and it is also uncertain whether or not the eradication of Clostridium, as seen in the UFSF treatment group, is a positive effect.…”
Section: Figsupporting
confidence: 80%
“…observed in these fermentations appear to be a normal part of the porcine healthy gut microbiota, as they were present in high numbers in the baseline group and grew to high numbers in the control group, an observation consistent with the findings of other studies in healthy animals (56,59,63,64). In the absence of genuine illness, the actual implications of Clostridium populations are difficult to discern, and it is also uncertain whether or not the eradication of Clostridium, as seen in the UFSF treatment group, is a positive effect.…”
Section: Figsupporting
confidence: 80%
“…Our deep 16S rRNA gene-sequencing approach detected 12 bacterial phyla in broilers, which was less than that previously detected in pigs (Buzoianu et al, 2012b(Buzoianu et al, , 2013. The main phyla identified were Firmicutes, Bacteroidetes, and Proteobacteria, and this was in agreement with previously reported data on the cecal microbiota of broilers using 16S rRNA gene sequencing (Qu et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…Many types of Bt-crops have been commercialized worldwide, triggering concerns about their potential impact on the health of humans and livestock. A large number of feeding studies have shown that the Cry proteins expressed by Bt-crops are non-toxic to humans and mammals (Kılıç et al, 2008;Buzoianu et al, 2013;Zeljenková et al, 2014). Diets containing Bt-corn had no deleterious effects on weight gain and carcass yields of broilers (Brake et al, 2003;Taylor et al, 2003;McNaughton et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The advent of high-throughput sequencing has facilitated comprehensive profiling of the resident bacteria in the digestive tracts of pigs (17,22,29,30). However, this study is one of the first to exploit this technology to examine the intestinal microbiota among pigs of varying FE.…”
Section: Discussionmentioning
confidence: 99%